2019
DOI: 10.1158/0008-5472.can-19-0991
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Genomic, Epigenomic, and Transcriptomic Aberrations during Stepwise Hepatocarcinogenesis

Abstract: Hepatocellular carcinoma (HCC) undergoes a stepwise progression from liver cirrhosis to low-grade dysplastic nodule (LGDN), high-grade dysplastic nodule (HGDN), early HCC (eHCC), and progressed HCC (pHCC). Here, we profiled multilayered genomic, epigenomic, and transcriptomic aberrations in the stepwise hepatocarcinogenesis. Initial DNA methylation was observed in eHCC (e.g., DKK3, SALL3, and SOX1) while more extensive methylation was observed in pHCC. In addition, eHCCs showed an initial loss of DNA copy numb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…63 Other studies highlighted that transcriptomic dysregulation of signalling pathways, such as TGFb, WNT, and NOTCH, as well as extensive epigenetic modifications occurred after malignant transformation, mainly in progressed HCC, confirming that genomic and epigenomic diversity occurred in the late stages of liver carcinogenesis. [94][95][96] Although recently our understanding of mutations and mutational signatures in human patients at different stages of liver disease has improved greatly, there remain key questions of how a…”
Section: Driver Mutations Involved In Tumour Initiation and Malignantmentioning
confidence: 99%
“…63 Other studies highlighted that transcriptomic dysregulation of signalling pathways, such as TGFb, WNT, and NOTCH, as well as extensive epigenetic modifications occurred after malignant transformation, mainly in progressed HCC, confirming that genomic and epigenomic diversity occurred in the late stages of liver carcinogenesis. [94][95][96] Although recently our understanding of mutations and mutational signatures in human patients at different stages of liver disease has improved greatly, there remain key questions of how a…”
Section: Driver Mutations Involved In Tumour Initiation and Malignantmentioning
confidence: 99%
“…The major risk factors for HCC include chronic infection of hepatitis B and C viruses (HBV and HCV), cirrhosis, alcohol abuse and non-alcoholic fatty liver disease (NAFLD) [2]. Hepatocarcinogenesis is characterized by dysregulated activation and/or expression of relevant genes in/on the hepatocytes, with resultant oncogene upregulation and tumor suppressor downregulation [3]. The last 5 decades has been characterized by discovery several biomarkers for diagnosis of HCC, including the α-fetoprotein (AFP), AFP-L3 (a heteroplast of AFP), des-γ-carboxyprothrombin (DCP), α-L-fucosidase (AFU), golgi protein 73 (GP73), osteopontin (OPN) and carbohydrate antigen 19-9 (CA19-9), which is globally regarded as diagnostic serological biomarkers for diagnosis of HCC patients.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatocarcinogenesis entails alteration of cellular gene expression with consequent loss of benignity, acquisition of malignant phenotype and enhancement of the aggressiveness of the resultant cancerous liver cells [3]. Previous studies have shown that ubiquitylation and SUMOylation are signi cantly enhanced in HCC [14].…”
Section: Discussionmentioning
confidence: 99%
“…The disease course and progression of HCC is facilitated by altered cellular gene expression with dysregulated metabolism and pathophysiological signaling pathways [3][4][5]. SUMOylation, a posttranslational modi cation that entails addition of small ubiquitin-like modi er (SUMO) groups to target proteins, is involved in numerous cellular events including transcriptional regulation, protein stability, cell cycle and apoptosis [10].…”
Section: Hccmentioning
confidence: 99%
See 1 more Smart Citation